Knowledge and Practice of Breast Self-Examination - Farwa Rizvi, Majeed Rajput, Muhammad Afzal (Journal of Rawalpindi Medical College, 2013)
Background: To determine knowledge and practice of breast self examination and risk factors for breast cancer. Methods: In this cross sectional study, 68 female medical students, doctors and nurses, using consecutive sampling technique (non probability) were enrolled and questions were asked to assess the knowledge about self breast examination and breast cancer.Close ended questionnaire was used as data instrument for the survey. Results: Thirty six (53%) were doctors, 23(34%) were nurses and 9 (13%) were medical students. Majority( 97%) of doctors, 96% nurses and 78% medical students had some information of breast self examination. Thirty five(97%) doctors, 18 (78%) nurses and only 6 (67%) medical students had actual knowledge of how to do breast self examination. Only 24 (67%) doctors, 9 (39%) nurses and 5 (56%) medical students actually performed breast self examination. All doctors (100%), 18 nurses (78%) and 7 medical students (78%) knew that mammography is a good tool for screening of breast cancer. All the doctors (100%) and greater part of the nurses (96%) had knowledge about different warning signs/symptoms of suspected breast cancer. Conclusion: There is a need for continuing medical education programs regarding breast cancer awareness and risk factors.